Rigidez passiva do quadril e resistência mecânica passiva do mediopé estão associadas aos movimentos do membro inferior no plano frontal e transverso durante a marcha - Thais Brasil Cardoso (2019)
Increased knee and hip internal rotation and foot eversion during closed-chain activities are associated with lower limb injuries, such as patellofemoral pain and plantar fasciitis. Thus, identifying factors related to these lower limb movement patterns might guide the assessment of individuals with increased hip and knee internal rotation and foot eversion during gait. Forefoot-shank alignment, midfoot passive mechanical resistance and hip external rotation passive stiffness may be associated with lower limb movements in the frontal and transverse planes during gait. This study investigated if these three factors are associated with foot eversion and knee and hip internal rotation during the stance phase of gait. Thirty healthy adults (18 females and 12 males) participated in this study. The hip external rotation passive stiffness was measured as the position of the first resistance detected during passive internal rotation with the participant positioned in the prone position. For measurement of the forefoot-shank alignment, participant remained in the prone position, with the assessed lower limb extended, with the ankle at 0° of plantar flexion and dorsiflexion. Upper view photographs were taken using a digital camera to calculate the angle formed between the forefoot and the bisection of the shank. The midfoot passive mechanical resistance was measured using the Torsimeter instrument, which is able to measure the torque passive resistance to forefoot inversion relative to the rearfoot. Kinematic data of the lower limbs during gait were collected using an 11-camera motion capture system Qualysis (Oqus 7+). Multiple stepwise linear regressions were used to identify if forefoot-shank alignment, midfoot passive mechanical resistance and hip external rotation passive stiffness are associated with ankle eversion and knee and hip internal rotation during the stance phase of gait. The level of significance was set at α = 0.05. Reduced midfoot passive torque was associated with greater hip range of motion (ROM) in the transverse plane, reduced midfoot passive stiffness was associated with greater knee internal rotation peak, greater midfoot passive torque and stiffness were associated with greater knee external rotation peak and reduced hip external rotation passive stiffness was associated with greater ankle ROM in the frontal plane. Forefoot-shank alignment was not included in any regression model. These findings demonstrate that individuals with reduced hip and midfoot passive stiffness have greater hip and knee internal rotation and greater ankle eversion and individuals with increased midfoot passive torque and stiffness have greater knee external rotation. These findings can be explained by the coupling between foot motion in the frontal plane and knee and hip movement in the transverse plane, and might guide the assessment of aspects of structure and body function in individuals with modifications of hip and knee movement in the transverse plane and motion of the foot in the frontal plane during gait.